Enhanced corticospinal excitability in the tibialis anterior during static stretching of the soleus in young healthy individuals. - Francesco Budini; Monica Christova (PLoS ONE)
Corticospinal excitability is known to be affected by afferent inflow arising from the proprioceptors during active or passive muscle movements. Also during static stretching (SS) afferent activity is enhanced, but its effect on corticospinal excitability received limited attention and has only been investigated as a single average value spread over the entire stretching period. Using transcranial magnetic stimulation (TMS) the present study was conducted to explore the time course of corticospinal excitability during 30 seconds SS. Motor evoked potentials (MEPs) after TMS were recorded from soleus (SOL) and tibialis anterior (TA) muscles in 14 participants during: a passive dynamic ankle dorsiflexion (DF), at six different time points during maximal individual SS (3, 6, 9, 18, 21 and 25 seconds into stretching), during a passive dynamic ankle plantar flexion (PF) and following SS. To explore the time course of corticospinal excitability during the static lengthened phase of a muscle stretch, the stretching protocol was repeated several times so that it was possible to collect a sufficient number of stimulations at each specific time point into SS, as well as during DF and PF. During passive DF, MEPs amplitude was greater than baseline in both TA and SOL (p = .001 and p = .005 respectively). During SS, MEPs amplitude was greater than baseline in TA (p = .006), but not in SOL. No differences between the investigated time points were found and no trend was detected throughout the stretching time. No effect in either muscle was observed during passive PF and after SS. These results could suggest that an increased activity of secondary afferents from SOL muscle spindles exert a corticomotor facilitation on TA. The muscle-nonspecific response observed during passive DF could instead be attributed to an increased activation within the sensorimotor cortical areas as a result of the awareness of the foot passive displacements.